2009
DOI: 10.1063/1.3125445
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic origins of the induced χ(2) in thermally poled phosphate glasses

Abstract: We have investigated the microscopic origins of the induced χ(2) in two phosphate glasses: a self-prepared lanthanum phosphate glass with molar composition 0.2La2O3 0.8P2O5 and a commercial sodium alumino phosphate glass (IOG-1, Schott Glass Technologies, Inc.) with molar composition 0.6P2O5 0.24Na2O 0.13Al2O3 0.03Ce2O3. The drastic difference in alkali content in these two phosphate glass systems results in different origins of their induced χ(2). For the poled lanthanum phosphate glass, the origin of the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…In this brief communication we present the results of polarization of phosphate glasses with different structures. Our results remarkably differ from the ones reported, for example, in [11,13].…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In this brief communication we present the results of polarization of phosphate glasses with different structures. Our results remarkably differ from the ones reported, for example, in [11,13].…”
contrasting
confidence: 99%
“…At the same time, poling of phosphate glasses has almost not been studied. There is a few works where it was found that subanodic layers in the poled phosphate glasses demonstrate SHG [11][12][13][14]. Unfortunately, the authors of these works do not present the time dependences of polarization current and other details of poling procedure.…”
mentioning
confidence: 99%
“…While much effort has been directed at studying poling‐induced surface layers in terms of second‐order nonlinear properties, a fundamental glass science question arises in exactly how the atomic structure accommodates the depletion of network‐modifying elements as mobile cations are driven to migrate out of the high‐field surface layer. Prior work focused on understanding of structure in poled layers have consistently shown evidence of network repolymerization within some depletion layers, including non‐bridging oxygen (NBO) elimination and densification in silicates and phosphates, changes in boron coordination in borate glasses, and oxygen release and/or electrode oxidation . A similar repolymerization effect has also been observed in alkali‐free aluminoborosilicate glasses .…”
Section: Introductionmentioning
confidence: 83%
“…This constitutes a specificity of the thin films’ thermal poling and cannot be explained by classical electrostatic models describing this treatment. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…The basic principle of this process is simple and has been applied to glasses to produce a SONL response since the beginning of the 1990s. [ 5 ] Thermal poling of a large variety of glass families has been examined, including all types of pure silica, [ 5–8 ] silicate, [ 9–12 ] phosphate, [ 13–16 ] germanate, [ 17,18 ] tellurite, [ 19–21 ] and chalogenide [ 22,23 ] materials, with this list being nonexhaustive. Various attempts have been made to develop optical devices relying on the SONL response of poled glasses with the glasses being either in the form of optical fibers [ 24,25 ] or in planar systems.…”
Section: Introductionmentioning
confidence: 99%